2013
DOI: 10.1007/s10457-013-9642-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rubber trees on leaf-miner damage to coffee plants in an agroforestry system

Abstract: The coffee leaf-miner (CLM) (Leucoptera coffeella Guérin-Mèneville; Lepidoptera: Lyonetiidae), the main pest of coffee plants, occurs widely throughout the Neotropics where it has a significant, negative economic and quantitative impact on coffee production. This study was conducted in a rubber tree/ coffee plant interface that was influenced by the trees to a varying degrees depending on the location of the coffee plants, i.e. from beneath the rubber trees, extending through a range of distances from the edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…According to Neves et al (2007), intercropping coffee plants in agroforestry systems entails water savings, and coffee transpiration has shown to be significantly reduced when it is grown in shade conditions (MORAIS et al, 2007). Righi et al (2013) studying coffee in a crop production system with rubber trees, found a higher CLM's incidence after periods with greater soil water deficiency, the same occurred in the present study. Coffee plants under lower water stress are less susceptible to attacks from CLM (MEIRELES; CARVALHO; MORAES, 2001;ASSIS et al, 2012), given that plants under water stress show greater levels of nitrogen and lower levels of secondary metabolites, which are attractive to the pest (LAWTON; MCNEILL, 1979).…”
Section: Pest Incidence and Microclimatessupporting
confidence: 88%
See 2 more Smart Citations
“…According to Neves et al (2007), intercropping coffee plants in agroforestry systems entails water savings, and coffee transpiration has shown to be significantly reduced when it is grown in shade conditions (MORAIS et al, 2007). Righi et al (2013) studying coffee in a crop production system with rubber trees, found a higher CLM's incidence after periods with greater soil water deficiency, the same occurred in the present study. Coffee plants under lower water stress are less susceptible to attacks from CLM (MEIRELES; CARVALHO; MORAES, 2001;ASSIS et al, 2012), given that plants under water stress show greater levels of nitrogen and lower levels of secondary metabolites, which are attractive to the pest (LAWTON; MCNEILL, 1979).…”
Section: Pest Incidence and Microclimatessupporting
confidence: 88%
“…The incidence of L. coffeella decreased as the rainfall increased, corroborating other studies that have shown a reduction in the leaf miner's survival rate during rainy periods (ANTUNES, 1986; LOMELÍ-FLORES; BARRERA; BERNAL, 2010; RIGHI et al, 2013). Pereira et al (2007) found that rainfall is one of the primary causes of mortality at the egg and especially larval stages, which occur during the rainy season.…”
Section: Effect Of Rainfall On Pest Incidencesupporting
confidence: 85%
See 1 more Smart Citation
“…The coffee leaf miner (CLM) Leucoptera coffeella (Lepidoptera: Lyonetiidae) is one of the key pests of coffee plantings and is reported in coffee growing regions throughout the world (PEREIRA et al, 2007;SCALÓN et al, 2011;RIGHI et al, 2013). The CLM larva mines the palisade parenchyma, prevents photosynthesis (NEVES et al, 2006), and may result in yield losses of 50% if control measures are not adopted (REIS & SOUZA, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The coffee leafminer Leucoptera coffeella (Guérin-Méneville, 1842) (Lepidoptera: Lyonetiidae) is originally from Africa and has become a pest species of great significance in many countries producing coffee (Coffea arabica and Coffea canephora) [1,2]. The extremely variable life cycle of this species and their damage to coffee crops make them a pest with a high destruction capacity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%